Proteomic Analysis of KCNK3 Loss of Expression Identified Dysregulated Pathways in Pulmonary Vascular Cells - Le Ribeuz, Hélène (Int J Mol Sci, 2020)
The physiopathology of pulmonary arterial hypertension (PAH) is characterized by pulmonary artery smooth muscle cell (PASMC) and endothelial cell (PAEC) dysfunction, contributing to pulmonary arterial obstruction and PAH progression. KCNK3 loss of function mutations are responsible for the first channelopathy identified in PAH. Loss of KCNK3 function/expression is a hallmark of PAH. However, the molecular mechanisms involved in KCNK3 dysfunction are mostly unknown. To identify the pathological molecular mechanisms downstream of KCNK3 in human PASMCs (hPASMCs) and human PAECs (hPAECs), we used a Liquid Chromatography-Tandem Mass Spectrometry-based proteomic approach to identify the molecular pathways regulated by KCNK3. KCNK3 loss of expression was induced in control hPASMCs or hPAECs by specific siRNA targeting KCNK3. We found that the loss of KCNK3 expression in hPAECs and hPASMCs leads to 326 and 222 proteins differentially expressed, respectively. Among them, 53 proteins were common to hPAECs and hPASMCs. The specific proteome remodeling in hPAECs in absence of KCNK3 was mostly related to the activation of glycolysis, the superpathway of methionine degradation, and the mTOR signaling pathways, and to a reduction in EIF2 signaling pathways. In hPASMCs, we found an activation of the PI3K/AKT signaling pathways and a reduction in EIF2 signaling and the Purine Nucleotides De Novo Biosynthesis II and IL-8 signaling pathways. Common to hPAECs and hPASMCs, we found that the loss of KCNK3 expression leads to the activation of the NRF2-mediated oxidative stress response and a reduction in the interferon pathway. In the hPAECs and hPASMCs, we found an increased expression of HO-1 (heme oxygenase-1) and a decreased IFIT3 (interferon-induced proteins with tetratricopeptide repeats 3) (confirmed by Western blotting), allowing us to identify these axes to understand the consequences of KCNK3 dysfunction. Our experiments, based on the loss of KCNK3 expression by a specific siRNA strategy in control hPAECs and hPASMCs, allow us to identify differences in the activation of several signaling pathways, indicating the key role played by KCNK3 dysfunction in the development of PAH. Altogether, these results allow us to better understand the consequences of KCNK3 dysfunction and suggest that KCNK3 loss of expression acts in favor of the proliferation and migration of hPASMCs and promotes the metabolic shift and apoptosis resistance of hPAECs.